2013
DOI: 10.1371/journal.pone.0069409
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Distinct Monocyte Subsets to Clinical Course of Ischemic Stroke Patients

Abstract: Background and PurposeThe most common strategy for treating patients with acute ischemic stroke is thrombolytic therapy, though only a few patients receive benefits because of the narrow time window. Inflammation occurring in the central nervous system (CNS) in association with ischemia is caused by immune cells including monocytes and involved in lesion expansion. If the specific roles of monocyte subsets in stroke can be revealed, they may become an effective target for new treatment strategies.MethodsWe per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 34 publications
4
81
0
1
Order By: Relevance
“…Indeed, Kaito et al showed that different monocyte subsets can have different role in AIS pathophysiology [47]. First, the small size (30 smokers and 59 nonsmokers enrolled) of a single-centre study may not represent the complexity of all AIS patients and, for this reason, the results cannot be extended to a general population.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Kaito et al showed that different monocyte subsets can have different role in AIS pathophysiology [47]. First, the small size (30 smokers and 59 nonsmokers enrolled) of a single-centre study may not represent the complexity of all AIS patients and, for this reason, the results cannot be extended to a general population.…”
Section: Discussionmentioning
confidence: 99%
“…About different subtypes, classical monocyte subset (CD14 ++ CD16 − ) significantly increased, while the non-classical monocyte subset (CD14 + CD16 ++ ) significantly decreased [29]. Progression and severity of brain ischemia directly correlate with CD14 ++ CD16 − increase and CD14 + CD16 ++ reduction [29]. As already known in another model [30], the splenic monocyte reserves were critical in the pathophysiology of brain infarction [31,32].…”
Section: Inflammatory Cells Involved In Post-ischemic Brain Injurymentioning
confidence: 95%
“…Early after brain injury, an increased number of total monocytes in the blood circulation has been described in humans [29]. About different subtypes, classical monocyte subset (CD14 ++ CD16 − ) significantly increased, while the non-classical monocyte subset (CD14 + CD16 ++ ) significantly decreased [29]. Progression and severity of brain ischemia directly correlate with CD14 ++ CD16 − increase and CD14 + CD16 ++ reduction [29].…”
Section: Inflammatory Cells Involved In Post-ischemic Brain Injurymentioning
confidence: 99%
“…Importantly, brain ischemia also triggers a systemic immune response. While blood lymphocyte numbers decline, levels of circulating neutrophils and monocytes increase in stroke patients 1, 2 . These myeloid cells are recruited to the brain 3 where they may contribute to the brain’s recovery but also to reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%